Socioeconomic impacts of cross-border transport infrastructure development in South Asia - John Gilbert; Nilanjan Banik (Asian Development Bank Institute (ADBI), 2010)
Although the overall economic performance of economies in South Asia in recent years has been impressive, there is concern that an aging and increasingly inadequate infrastructure may limit the potential for further growth and economic development. A critical infrastructure component is the transportation network, and there are currently several transportation infrastructure projects in the South Asia Subregional Economic Cooperation (SASEC) region, connecting Nepal, eastern India, Bangladesh, and Bhutan. This paper uses computable general equilibrium (CGE) methods to address how these infrastructure developments might affect the broader economy in SASEC, and in particular impact on income distribution and poverty. The paper describes a new CGE model for South Asia, covering India, Sri Lanka, Bangladesh, Nepal, and Pakistan, which incorporates modifications to household structure in order to capture the implications of reform for changes in intra-household income. The scenarios that are considered reflect proposed investments in land transport infrastructure in the SASEC region. These should result in reductions in the land transport component of international transport margins, which vary bilaterally by commodity. We found that all SASEC economies would benefit from the reductions in terms of aggregate welfare, with the largest gains accruing to India in absolute terms, but the largest relative gains to Nepal, followed by Bangladesh and Sri Lanka when the margin reduction is prorated to intra-South Asian trade rather than just SASEC. In terms of household level distribution, the picture was mixed, with clearly pro-poor outcomes in some countries, such as Nepal, but more ambiguous impacts in others. In terms of potential adjustment costs, examination of the extent of predicted structural changes suggests that these would be minor, although somewhat more significant for the smaller economies in the region.
Keywords: F14; F17; D58; O53; 330; Infrastrukturinvestition; Grenzüberschreitender Verkehr; Makroökonomischer Einfluss; Einkommensverteilung; Armut; Allgemeines Gleichgewicht; Indien; Sri Lanka; Bangladesch; Neapel; Pakistan